Ritual Batak Manulangi dalam Budaya Batak Sebagai Pastoral Indigenous di Huria Kristen Batak Protestan - Damai Yanti Sinaga; Azwar Anas Pasaribu; Samuel Deutschland Sigalingging (Universitas Negeri Medan, 2021)
This article aims to explore the meaning and purpose of manulangi and to discover the values of local wisdom that can be used as a means of pastoral care. The pastoral approach through adat is possible because the Batak people are always bound by adat, even though they live in the village or migrate to other places. The research method was carried out by qualitative and data collection techniques were carried out through semi-structured interviews or in-depth interviews and literature study and data analysis was carried out by flow analysis, namely collecting, processing, and drawing conclusions. Through this method it was found that the purpose of the manulangi was to honor the parent at the end of his life, asking for blessings and thanks. In addition, the values of kinship, solidarity and care, politeness and openness were found. In addition, values that contain pastoral dimensions such as; sustaining, healing and reconciling and guiding. Based on all of these values, manulangi can be applied as a means of pastoral assistance for parents who are sick due to illness, old age and family. As well as prayer and communion, can be integrated as a holistic and holistic pastoral care for PTI and its families.